Aspectos das Condições e Organização do Trabalho na Ocorrência de Acidentes entre Profissionais da Enfermagem - Almussa, Aline [UNESP]; Schmidt, Maria Luiza Gava [UNESP] (My University, 2011)
The article had how purpose identify aspects about the conditions and the work organization that influenced on work accidents occurrences among nurses’ professionals, well as: to identify the workers’ perceptions about work accidents occurrences; to collaborate for reduction of the cases of work accidents; to co-operate with technical-scientific information for comprehension of health damages of worker population. The research was realized in a Hospital Institution in the interior of the State of São Paulo. It was interviewed: 45 nurses’ adjutants; 44 nurses’ technician; 11 nurses, using semi-structured individuals interviews. The qualitative analyses had the Dejours’s Psychodynamic of Work how reference. Partial results reveal that organizations problems as well: banks of hours; deficient functional framework, overload work; insufficient sleep hours; double day journey; ergonomics problems; lack of security equipments, appear how the principal indicators related of work accidents occurrences.

El artículo tuvo como objetivo identificar los aspectos de las condiciones y organización del trabajo que influyen en la ocurrencia de accidentes de trabajo entre los profesionales de enfermería, así como: identificar las percepciones de los empleados sobre su incidencia; contribuir con información técnica y científica para la comprensión de los problemas de salud de los trabajadores. Los datos fueron recolectados en un hospital en el estado de São Paulo. Fueron entrevistados: 45 auxiliares de enfermería, 44 técnicos y 11 enfermeiros a través de entrevistas individuales semi-estructuradas. El análisis cualitativo, como una referencia a la psicodinámica del trabajo de Dejours. Los resultados mostraron que los problemas de organización, tales como: bancos de horas; discapacidad en el personal; sobrecarga de trabajo; insuficiencia de horas de sueño; doble días; problemas de la ergonomía; y falta de equipo de seguridad, aparecen como los principales indicadores relacionados con la ocurrencia de accidentes.

O artigo objetivou identificar aspectos das condições e da organização do trabalho que influenciem as ocorrências de Acidentes de Trabalho (AT) entre profissionais da enfermagem, bem como: identificar as percepções dos trabalhadores sobre a ocorrência de AT no contexto estudado; contribuir com informações técnico-científicas para compreensão dos agravos à saúde dos trabalhadores. Os dados foram coletados numa instituição hospitalar no interior do estado de São Paulo. Foram entrevistados: 45 auxiliares de enfermagem, 44 técnicos e 11enfermeiros, através de entrevistas individuais semi-estruturadas. A analise qualitativa, tomou como referência a Psicodinâmica do Trabalho de Dejours. Resultados revelaram que problemas organizacionais como: bancos de hora; deficiência no quadro funcional; sobrecarga de trabalho; horas de sono insuficientes; duplas jornadas; problemas de ergonomia; falta de equipamentos de segurança, aparecem como principais indicadores relacionados às ocorrências de AT.
Keywords: Work Organization; Work Accidents; Nursing Professional; Organización del trabajo; Accidentes industriales; Profesionales de enfermería; Organização do trabalho; Acidentes de trabalho; Profissionais da Enfermagem